(untitled) (Ágora de Heterodoxias, 2026)
This study on community-based tourism in Temoaya was conducted to gain a comprehensive understanding of the perceptions, opinions, and conditions affecting the communities involved in the region’s tourism development. The problem lies in the lack of social cohesion, evident not only in the perceptions of social actors but also in the absence of tourism policies based on solidarity principles The research is based on the critical-reflective approach, which includes the methodological process of the co-implicated model. The main findings reveal not only a perceived lack of social cohesion among the various stakeholders but also the need to design targeted policies and programs to promote and develop community-based tourism in Temoaya, Mexico.